2015
DOI: 10.1007/s00270-015-1119-y
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Recanalization of Chronically Occluded Native Arteries After Failed Bypass Surgery in Patients with Critical Ischemia

Abstract: Endovascular recanalization of native CTO in patients with graft failure-related CLI is a feasible, safe, and effective procedure, with reasonable technical success, vessel patency, and limb salvage rates. The technique should be attempted before amputation in patients with limited surgical revascularization options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…As another study showed, the reduced primary patency of diabetics is most likely due to their advanced stage at presentation . In terms of anastomosis occlusion, another risk factor, our finding (HR 2.877; 95% CI 1.1‐6.7, P = 0.029) was similar to that of Yin et al study (HR 2.84; 95% CI 1.00‐8.03, P = 0.049) . The effect of this factor was only found to be significant in univariate analysis.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…As another study showed, the reduced primary patency of diabetics is most likely due to their advanced stage at presentation . In terms of anastomosis occlusion, another risk factor, our finding (HR 2.877; 95% CI 1.1‐6.7, P = 0.029) was similar to that of Yin et al study (HR 2.84; 95% CI 1.00‐8.03, P = 0.049) . The effect of this factor was only found to be significant in univariate analysis.…”
Section: Discussionsupporting
confidence: 85%
“…34 In terms of anastomosis occlusion, another risk factor, our finding (HR 2.877; 95% CI 1.1-6.7, P = 0.029) was similar to that of Yin et al study (HR 2.84; 95% CI 1.00-8.03, P = 0.049). 30 The effect of this factor was only found to be significant in univariate analysis. As is demonstrated in many studies, anastomotic lesions may negatively influence the results of revision of failed vein bypass graft.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations